PERSEPSI GURU PENJAS SEKOLAH DASAR TERHADAP ANAK GEMUK DI KECAMATAN SEMARANG TENGAH - Metta Christiana; Andi Nurcahyo (Universitas Semarang, 2018)
The purpose of this study was to find out how the perceptions of primary school teachers in Central Semarang District were. This type of research is qualitative with a phenomenological approach. Data was collected by in-depth interview and observation methods. Research subjects were 8 people consisting of 3 health teachers, 3 regular teachers, 1 vice principal and 1 principal. Data were analyzed by means of content analysis. The results showed that the perceptions of the primary school teachers in Central Semarang Subdistrict showed concern about the condition of obese children while doing material in sports lessons, but the teacher also felt very happy and excited about the fat child. The feeling of excitement and excitement is still quite large so that the feeling of worry is not too big. The teacher is still considering the child's obesity is not a problem if the fat child can still do sports / movement material well not inferior to other children. The teacher also does not have great hopes / desires / motivations so that the fat child is less fat and becomes normal again. Perceptions like this will make the teacher's action not too strict / not too strong in overcoming child obesity problems.